Dynamic behavior of reinforced concrete beams under varying rates of concentrated and impact loadings - Satadru Das Adhikary (2014)
Reinforced Concrete (RC) structures may experience various types of loading during their lifespan, which in turn induces a wide spectrum of strain rates. The materials involved in RC structures are strain-rate sensitive and thus, the behavior of structural members can be affected by the loading rates but only significantly when the rate differs by more than one order of magnitude. Majority of past research on RC beams have focused on assessing their behavior under static and relatively slow loading rates while limited attention has been paid to the high loading rates. Therefore, to shed some light in this field, an experimental program comprising twenty-four RC beams was carried out under four different loading rates ranging from slow (4 10-4 m/s) to fast (2 m/s) to cover the wide range of loading scenarios (quasi-static, earthquakes and low velocity impact regime). Comparative analyses of beams under these varying loading rates highlighted several important aspects of their dynamic behavior. Furthermore, the influence of various key parameters on dynamic increase factor (DIF) of maximum resistance and failure modes of beams under these loading conditions was summarized and discussed through numerical simulation parametric studies after successful validation of numerical models in an explicit finite element (FE) program. Although the loading rate effects covering low velocity impact regime were considered, however, it would be more practical to consider realistic impacts. Thus, a drop-weight impact test program was undertaken on thirty RC beams to evaluate their impact responses. The acquired data was then used in the development and verification of numerical and analytical methods. Two empirical equations have been proposed by analyzing a dataset which would aid in determining the required static bending and shear resistance for input impact energy by specifying the maximum midspan deflection for each limit state of beam. Moreover, to extent the knowledge beyond the range of parameters investigated experimentally, FE models of the beams were also developed. Maximum midspan deflection could be an important performance index to evaluate the damage levels of beam when subjected to impact loadings; hence simplified analytical models were employed to predict the same in less modeling effort and computational time. Residual performance assessment of damaged structures has been gaining enormous importance in engineering community to ensure that the damaged structures will not fail catastrophically and uphold structural integrity. However, to date no study has been documented in literature on residual performance of impact-damaged RC beams. Thus, the impact-damaged beams have been retested quasi-statically to determine their post-impact residual responses. Finally, the FE models developed earlier for drop-weight impact loading were modified by replacing the impactor with the loading plate to perform quasi-static simulation by utilizing resulting deformation and damages of beams from the impact stages. Thereafter, these models were used further to quantify the effect of various parameters on residual resistance index (RRI), which could be used effectively to delineate the extents of damage of beams after impact.